Early Childhood Learning Losses during COVID-19: Systematic Review - Ugras, Mustafa; Zengin, Erdal; Papadakis, Stamatis; Kalogiannakis, Michail (Mdpi, 2023)
The global education system has been significantly disrupted by COVID-19, and researchers are concerned with the impact this has had on students who have experienced learning loss. This study aims to systematically review the articles published in Science Direct, Wiley Online Library, SpringerLink, Sage Journals, Taylor & Francis Online, ERIC, JSTOR and Google Scholar on learning loss experienced by students in early childhood during the COVID-19 pandemic between 2020 and 2023. We conducted a systematic literature review of 33 articles published in the Web of Science (WOS), ERIC and Google Scholar electronic databases between 2020 and 2023. The review found a significant increase in early childhood learning losses. In addition, the present study found an increase in inequality, while certain demographic groups experienced more learning loss than others.
Keywords: COVID-19; early childhood education; learning loss; systematic literature review